Produção e caracterização de nanopartículas de BaTiO3 através da rota sol-gel utilizando substâncias húmicas provenientes da água de rio - Lima, Camila Higina Santos (2017)
The goals of the present work consisted in the production of nanoparticles of pure barium titanate and doped with Nd, by means of an unpublished route that uses humic substances as complexing agent of the metalic ions and in the investigation of the influence of the synthesis parameters on the structural properties, on the crystalization of the material and on the luminescent properties of doped samples. Barium titanate (BaTiO 3 ) has potential for application in electro-optical devices, sonars, infrared sensors and multilayer capacitors. Parameters such as concentration, pH and calcination temperature were investigated during production, with the purpose of developing a simple, efficient and low energy cost procedure. The synthesis route proposed in this work was very promising in the production of BaTiO 3 . The samples produced with concentration of 0.5 g/ml presented a single tetragonal phase after calcination at 1200 ºC/5h. The crystallite size was estimated by Scherrer equation at around 28 nm and the particles were spherical, rod and needle shaped. The samples of pH 7 and 10 presented a single phase at 1100 ºC/5h and the samples doped with Neodymium presented a single phase at 1200 ºC/5h and a crystallite size estimated at 22 nm. In addition, the luminescent properties of the doped samples were studied, which were presented in accordance with the neodymium emission bands in the BaTiO 3 matrix.